2019
DOI: 10.1002/1873-3468.13641
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐gated sodium channels β3 subunit promotes tumorigenesis in hepatocellular carcinoma by facilitating p53 degradation

Abstract: The voltage‐gated sodium channels (VGSCs) are aberrantly expressed in a variety of tumors and play an important role in tumor growth and metastasis. Here, we show that VGSCs auxiliary β3 subunit, encoded by the SCN3B gene, promotes proliferation and suppresses apoptosis in HepG2 cells by promoting p53 degradation. β3 significantly increases HepG2 cell proliferation, promotes tumor growth in mouse xenograft models, and suppresses senescence and apoptosis. We found that β3 knockdown stabilizes p53 protein, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The role of SCN3B in p53-dependent cellular physiology is obscure. According to one report, it promotes p53-dependent apoptosis [126], and according to another report, it may be an element of the negative-feedback loop in the p53 signaling pathway [127]. Even though the expression of another gene, GABRD, regulating the transport of molecules across plasma membrane was not reported to be p53-dependent in any individual report, the gene was found to be activated by p53 in 12 high-throughput studies, and the enhancer of the gene is bound by p53 [18].…”
Section: Atypical Targets Of P53mentioning
confidence: 99%
“…The role of SCN3B in p53-dependent cellular physiology is obscure. According to one report, it promotes p53-dependent apoptosis [126], and according to another report, it may be an element of the negative-feedback loop in the p53 signaling pathway [127]. Even though the expression of another gene, GABRD, regulating the transport of molecules across plasma membrane was not reported to be p53-dependent in any individual report, the gene was found to be activated by p53 in 12 high-throughput studies, and the enhancer of the gene is bound by p53 [18].…”
Section: Atypical Targets Of P53mentioning
confidence: 99%
“…Surprisingly, a recent work on hepatocellular carcinoma (HCC) found contrasting results with the pro-apoptotic function of VGSCs β3-subunit. By using HepG2, a HCC cell line, Li and cols (Li et al, 2020) demonstrated that β3 subunit knockdown induces cell cycle arrest in HepG2 cells and attenuates tumor growth in nude mice. In addition, their findings indicate that β3 could bind to p53, which promotes its ubiquitination and degradation, leading to a lower level of p53.…”
Section: Resisting Apoptosismentioning
confidence: 99%
“…These contrasting results could be due to the molecular regulation of p53 ubiquitination and degradation carried by MDM2, a negative regulator of this tumor suppressor (Koo et al, 2022). The binding of β3 to p53 could stabilize the p53/ MDM2 complex promoting p53 ubiquitination and degradation (Li et al, 2020), whereas the exogenous overexpression of β3 could competitively promote the release of p53 from such complex and apoptosis in Saos-2 and T98G cells (Adachi et al, 2004). An additional study showed that β3 expression was totally absent in two metastatic BCa cell lines, whereas the other three VGSCs βsubunits were present at different levels of expression (Chioni et al, 2009).…”
Section: Resisting Apoptosismentioning
confidence: 99%
“…The sodium voltage-gated channel beta subunit 3 (SCN3B) controls electrolytes and contributes to the pacemaking in the heart and has an effect on intracellular trafficking (Ishikawa et al, 2012). It also suppresses senescence and apoptosis via its interaction with p53 and thus, is considered to be an oncogenic factor (Li et al, 2020).…”
Section: Scn3b (-)mentioning
confidence: 99%